Effectiveness of MR angiography for the primary diagnosis of acute pulmonary embolism: Clinical outcomes at 3 months and 1 year. Issue 4 (1st April 2013) - Schiebler, Mark L.; Nagle, Scott K.; François, Christopher J.; Repplinger, Michael D.; Hamedani, Azita G.; Vigen, Karl K.; Yarlagadda, Rajkumar; Grist, Thomas M.; Reeder, Scott B.
<x xml:space="preserve">Abstract</x> Purpose To determine the effectiveness of MR angiography for pulmonary embolism (MRA‐PE) in symptomatic patients. Materials and Methods We retrospectively reviewed all patients whom were evaluated for possible pulmonary embolism (PE) using MRA‐PE. A 3‐month and 1‐year from MRA‐PE electronic medical record (EMR) review was performed. Evidence for venous thromboembolism (VTE) (or death from PE) within the year of follow‐up was the outcome surrogate for this study. Results There were 190 MRA‐PE exams performed with 97.4% (185/190) of diagnostic quality. There were 148 patients (120 F: 28 M) that had both a diagnostic MRA‐PE exam and 1 complete year of EMR follow‐up. There were 167 patients (137 F: 30 M) with 3 months or greater follow‐up. We found 83% (139/167) and 81% (120/148) MRA‐PE exams negative for PE at 3 months and 1 year, respectively. Positive exams for PE were seen in 14% (23/167). During the 1‐year follow‐up period, five patients (false negative) were diagnosed with DVT (5/148 = 3.4 %), and one of these patients also experienced a non–life‐threatening PE. The negative predictive value (NPV) for MRA‐PE was 97% (92–99; 95% CI) at 3 months and 96% (90–98; 95% CI) with 1 year of follow‐up. Conclusion The NPV of MRA‐PE, when used for the primary diagnosis of pulmonary embolism in symptomatic patients, were found to be similar to the published values for CTA‐PE. In addition, the technical success rate and safety of MRA‐PE were excellent. J. Magn. Reson. Imaging 2013;38:914–925. © 2013 Wiley Periodicals, Inc.